Artificial intelligence, social media, and intelligent learning: effects on academic performance and mental well-being of accounting students - Luza, Bruna; Falconi, Tamara Gonçalves; Toigo, Leandro Augusto; Martins, Vinicius Abilio (REVISTA AMBIENTE CONTÁBIL - Universidade Federal do Rio Grande do Norte - ISSN 2176-9036, 2026)
Purpose: To investigate accounting students' perceptions concerning the effect of artificial intelligence (AI) and social media use on their academic performance and mental well-being, as well as to examine the mediating effect of intelligent learning on these relationships. Methodology: The study adopted a quantitative approach, using a structured questionnaire to 222 undergraduate accounting students from universities located in the western and southwestern regions of Paraná. Data were analyzed using structural equation modeling through the partial least squares method (PLS-SEM). Results: The results indicate that students perceive AI as a resource that favors their academic performance, but not their mental well-being. In contrast, social media, despite not influencing performance, demonstrated a relevant effect in promoting mental well-being. It was found that intelligent learning mediates the effects of AI on academic performance and social media on mental well-being, indicating that their effects manifest themselves when they are aligned with the contribution of each technology, cognitive in AI and emotional in social media. Contributions of the Study: The study contributes by highlighting the effects of AI and social media on teaching, with intelligent learning acting as a mediator. It is evident that these technologies tend to support different aspects of the educational process, with AI associated with cognitive aspects and social media with the socio-emotional aspects of the learning experience. The conclusions can guide pedagogical practices aligned with students' perceptions and reinforce the integration of technology and emotional support in promoting students' mental well-being.